Taxation and economic development in tropical Africa - Due, John F. (Cambridge, Mass. : M.I.T. Press, 1963)
This volume is based on a series of lectures given by author during the week of December 3-7, 1962 at Cambridge, under the auspices of the Harvard Law School International Program in Taxation and the M.I.T School of Industrial management.
"Based on a series of lectures given ... during the week of December 3-7, 1962, at Cambridge, under the auspices of the Harvard Law School International Program in Taxation and the M.I.T. School of Industrial Management."
Includes bibliographical references and index.
gp 24/01/2019
Loans
Keywords: Taxation